History of the Alps, 1500-1900 : environment, development, and society - Mathieu, Jon (Book collections on Project MUSE., 2009)
"In the 1700s, Jean-Jacques Rousseau celebrated the Alps as the quintessence of the triumph of nature over the "horrors" of civilization. Now available in English, History of the Alps, 1500-1900: Environment, Development, and Society provides a precise history of one of the greatest mountain range systems in the world. Jon Mathieu's work disproves a number of commonly held notions about the Alps, positioning them as neither an inversion of lowland society nor a world apart with respect to Europe. Mathieu's broad historical portrait addresses both the economic and sociopolitical - exploring the relationship between population levels, development, and the Alpine environment, as well as the complex links between agrarian structure, society, and the development of modern civilization. More detailed analysis examines the relationship between various agrarian structures and shifting political configurations, several aspects of family history between the late Middle Ages and the turn of the twentieth century, and exploration of the Savoy, Grisons, and Carinthia regions."--Cover description.